2009
DOI: 10.1016/j.dyepig.2008.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel photochromic 2,2′-bithiophene azo dyes

Abstract: The photochromic behaviour of two series of 2,2'-bithiophene azo dyes in THF solutions was studied. The photochromic properties and colour constancy were strongly dependent on the substitution pattern of the dyes. Under visible irradiation (> 420 nm) while some dyes exhibited a significant change in the colour intensity others exhibited an almost stable absorption. The photokinetic parameters of these systems are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…[29][30] In the last years we have synthesized a large variety of heterocyclic azo dyes substituted by electron-donating and electron-withdrawing groups ('push/pull' substitution pattern) that possess solvatochromic, photochromic and nonlinear optical (NLO) properties which are influenced by the electronic nature of the -conjugated bridge (thienylpyrrole or bithiophene) and by the substitution pattern on the aryl and heteroaryl-diazene moieties (Figure 1). [31][32][33][34][35][36][37][38] Figure 1 Earlier, we observed that bithiophene azo dyes exhibit photochromic properties at room temperature, although the speed of the photo and thermal isomerization is quite slow: visible light irradiation of phenyl substituted 2,2'-bithiophene azo dyes, in solution, leads in less than 30 s to a significant decrease of the absorbance at  max (35-50%) due to the conversion of the E-isomer to the Z-isomer. When the irradiation ceases the system returns to the initial state following a mono-exponential kinetics with an half-life time between 18 to 69 s, depending on the aryl substituents.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations
“…[29][30] In the last years we have synthesized a large variety of heterocyclic azo dyes substituted by electron-donating and electron-withdrawing groups ('push/pull' substitution pattern) that possess solvatochromic, photochromic and nonlinear optical (NLO) properties which are influenced by the electronic nature of the -conjugated bridge (thienylpyrrole or bithiophene) and by the substitution pattern on the aryl and heteroaryl-diazene moieties (Figure 1). [31][32][33][34][35][36][37][38] Figure 1 Earlier, we observed that bithiophene azo dyes exhibit photochromic properties at room temperature, although the speed of the photo and thermal isomerization is quite slow: visible light irradiation of phenyl substituted 2,2'-bithiophene azo dyes, in solution, leads in less than 30 s to a significant decrease of the absorbance at  max (35-50%) due to the conversion of the E-isomer to the Z-isomer. When the irradiation ceases the system returns to the initial state following a mono-exponential kinetics with an half-life time between 18 to 69 s, depending on the aryl substituents.…”
Section: Methodsmentioning
confidence: 95%
“…As a result a noticeable colour intensity change is easily perceivable by a naked eye, due to the switching between the two isomers. 38 In order to increase the speed of this process we decided to substitute the phenyl ring by thiazole, benzothiazole or thiadiazole heterocycles which are known to have a marked influence on the thermal stability of the Z-isomer. 33,35 The thiazolyl-, benzothiazolyl-and dithiazolyl-2,2'-bithiophene azo dyes presented in this study can be divided in four groups according to the nature of the aromatic ring linked to the azo group and the position of that linkage ( Figure 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Azo dyes constitute a dominant class of synthetic dyes. These azo dyes exist stably in the trans-isomers form but can be photochemically converted into the cis-isomers form without any bond breakage, leading to a realignment of the molecular structure and an observable change in the UV absorption spectra (1)(2)(3). Because of their characteristic photochromism, azo dyes are widely used in optical memory, optical switches, information converters and ophthalmic sun-screening applications and are also potentially useful in security printing, solar energy, storage, nonlinear optics and biological systems (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%